EDUKASI PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DALAM PENCEGAHAN SCABIES PADA SANTRI - Joni Siagian; Sri Legawati; Amelia Dini Anggraini Silalahi; Efi Irwansyah Pane; R Sri Rezeki; Yuriansyah; Muhammad Arif Simangungsong; Sri Julita (LPPM AKPER GITA MATURA ABADI KISARAN, 2026)
The high density of occupancy in Islamic boarding schools and limited hygiene facilities often lead to high rates of skin disease transmission, particularly scabies. The purpose of this community service program is to increase knowledge and change the behavior of students through Clean and Healthy Living Behavior (PHBS) Education as an effort to prevent scabies at the Bina Ulama Kisaran Islamic Boarding School. The activity was attended by 79 students and was implemented through the stages of survey, preparation, intervention, and monitoring and evaluation. The intervention was carried out using an interactive lecture method using PowerPoint presentations and posters, followed by a prevention simulation. Evaluation was measured using pre-test and post-test questionnaires and post-activity behavioral observations. The results of the community service program showed a significant increase in students' knowledge, with the overall average score increasing from 49% (pre-test) to 87% (post-test). Students also began implementing a zero-sharing policy and routinely drying mattresses. As a curative follow-up, students with symptoms were given 5% Permethrin cream. Conclusion: Visual media-based education has proven effective in improving cognitive aspects and triggering initial behavioral changes in students. The program's sustainability is supported by the commitment of caregivers through the planned formation of a health cadre for the Islamic boarding school.